Imiona poznaniaków u progu XVII stulecia (na materiale Akt sądu wójtowskiego) - Banderowicz, Kinga (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The subject matter of the studies presented in the article are the names of Poznań inhabitants from the beginning of the 17th century, excerpted from a manuscriptal source. The courtly records Akta sądu wójtowskiego present the official and formal variety of the language and consist of the records of court trials. The onyms confirmed in the source render the description of the then name system feasible. It was characterised by the choice of one name, the origin from the Christian antrophonomasticon, the attachment to the onomatologic tradition as well as great popularity of the most fashionable names.